Ocular Salvage in Serratia marcescens-Associated Odontogenic Orbital Abscess: Unmasking Latent Diabetes Mellitus and the Role of Immunoparesis - Sari Wulan Dwi Sutanegara; Ni Luh Sartika Sari; I Putu Yupindra Pradiptha; Disa Saraswati (HM Publisher, 2026)
Odontogenic sinusitis accounts for up to 40 percent of chronic maxillary sinusitis cases. While typically polymicrobial, the isolation of Serratia marcescens, an opportunistic Enterobacteriaceae, is an aberration in community settings and often signals profound underlying immunodeficiency. This report documents a rare case of Serratia-induced subperiosteal orbital abscess that unmasked latent type 2 diabetes mellitus. A 64-year-old male farmer presented with unilateral proptosis, ophthalmoplegia (frozen globe), and severe orbital pain following chronic odontogenic symptoms. Initial assessment revealed a random blood glucose of 500 mg/dL and glycated hemoglobin of 11.5 percent, confirming undiagnosed type 2 diabetes mellitus. Computed Tomography demonstrated a right maxillary abscess with osteolytic destruction of the lamina papyracea and an extraconal collection. Microbiological analysis of deep tissue biopsy via Vitek 2 confirmed Serratia marcescens while histopathology ruled out invasive fungal sinusitis. Management involved a dual-front strategy: rapid glycemic stabilization and broad-spectrum antibiotics, followed by functional endoscopic sinus surgery and dental extraction on Day 3. Post-operative follow-up showed resolution of proptosis from 24 mm to 16 mm, restoration of intraocular pressure from 32 mmHg to 14 mmHg, and improvement in visual acuity from light perception to 6/18. In conclusion, the isolation of Serratia marcescens in odontogenic sinusitis serves as a sentinel marker for metabolic dysregulation. This case highlights the synergistic lethality of neglected dental pathology and diabetic immunoparesis. Early recognition, exclusion of fungal mimics, and aggressive multidisciplinary intervention are paramount for ocular salvage.